A rare case of isochromosome 10: i(10p) and i(10q). Issue 1 (January 2015) - Elbastawisy, Hanan I.; Ghaly, Samuel W.; Abualhasan, Sawsan J.
Abstract : This is a report of a rare case of de-novo apparently balanced isochromosome 10, i(10p) and i(10q), diagnosed by fluorescence in-situ hybridization technique, in a preterm male baby (33 weeks) with birth weight 1.8 kg and multiple congenital anomalies such as single umbilical artery, dysmorphic facial features in the form of hairy forehead, low-set posteriorly rotated ears, bifid antitragus bilaterally, severe micrognathia, cleft palate, and short webbed neck. Both hands showed three rays of fingers with small proximally placed thumbs, partial syndactyly of second/third fingers and third/fourth fingers, bilateral simian creases, and very short lower limbs. The external genitalia showed hypoplastic dark scrotum with normal-sized phallus; left testis was felt along the inguinal canal, whereas the right one was not palpable, with anteriorly displaced anus. There was no history of consanguinity or of a similar condition in the family.